2007
DOI: 10.1152/ajpgi.00019.2007
|View full text |Cite
|
Sign up to set email alerts
|

Distension during gastroesophageal reflux: effects of acid inhibition and correlation with symptoms

Abstract: We studied spontaneous gastroesophageal reflux (GER)-induced esophageal distension using ultrasound imaging and its role in the genesis of esophageal symptoms before and during esomeprazole therapy. Ten controls and 10 GER disease (GERD) patients were studied by combined impedance, esophageal pH, manometry, and ultrasonography before and during esomeprazole therapy. Physiological data and symptoms were recorded for 2 h following a standardized meal. From ultrasound images, the esophageal cross-sectional area (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
(31 reference statements)
3
24
0
1
Order By: Relevance
“…A recent study by Schiffner et al (48,49) has shown that, in GERD patients without an obvious HH, the higher level of distension observed after opening could be traced back to an abnormally high radius to the circular muscle in the resting state and that, during opening, the muscularis continues to distend abnormally. When fully open, the difference was ϳ2.1 mm, consistent with a 2.5-mm difference between a normal and HH group at maximum mechanical distension of the GES and a 2.1-mm difference at maximum opening during reflux between a normal and GERD group as measured by other investigators (43,54). However, Schiffner et al (48,49) found that, in the resting state, the average radius to the inner surface of the circular muscle was ϳ1.2 mm greater in the GERD group compared with that in normal controls.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…A recent study by Schiffner et al (48,49) has shown that, in GERD patients without an obvious HH, the higher level of distension observed after opening could be traced back to an abnormally high radius to the circular muscle in the resting state and that, during opening, the muscularis continues to distend abnormally. When fully open, the difference was ϳ2.1 mm, consistent with a 2.5-mm difference between a normal and HH group at maximum mechanical distension of the GES and a 2.1-mm difference at maximum opening during reflux between a normal and GERD group as measured by other investigators (43,54). However, Schiffner et al (48,49) found that, in the resting state, the average radius to the inner surface of the circular muscle was ϳ1.2 mm greater in the GERD group compared with that in normal controls.…”
Section: Discussionsupporting
confidence: 82%
“…3-5 indicate that the existence of abnormally high levels of liquid within the GES, perhaps associated with an abnormality in the anatomy of the GES, is a controlling element that distinguishes normal opening from pathological opening and reflux. Studies comparing GERD groups with controls have shown that, when the relaxed sphincter is opened, the opening diameter of the hiatus is higher in the GERD groups (43,54). A recent study by Schiffner et al (48,49) has shown that, in GERD patients without an obvious HH, the higher level of distension observed after opening could be traced back to an abnormally high radius to the circular muscle in the resting state and that, during opening, the muscularis continues to distend abnormally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The average concentration of pepsin in gastric juice has previously been suggested to be approximately 0.5 mg/mL [30]. Reflux volumes could be virtually zero (e.g., aerosolised fluid brought up with a belch) or up to around 5.0 mL outside of mass regurgitation events [31]. There is approximately 0.8 mL of saliva/moisture in the oral cavity at any one time [32], which might dilute very low volume reflux events and therefore reduce [pepsin] saliva below a detectable limit.…”
Section: Discussionmentioning
confidence: 99%